1994
DOI: 10.1227/00006123-199410000-00015
|View full text |Cite
|
Sign up to set email alerts
|

The Application Accuracy of Stereotactic Frames

Abstract: The purpose of incorporating stereotactic methodology into neurosurgical operations is to achieve a consistently high degree of accuracy in localizing intracranial targets. Therefore, the limits of resolution for the operation are a function of the accuracy of the particular stereotactic frame system. The total clinically relevant error (application accuracy) comprises errors associated with each procedural step, including imaging, target selection, vector calculations, and the mechanical errors of stereotacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 352 publications
(70 citation statements)
references
References 23 publications
3
62
0
5
Order By: Relevance
“…The accuracy of stereotactic procedures has been extensively studied [2,3,4,5,6,7,8,9,10,11,12]. However, technology is evolving rapidly in terms of both the surgical equipment and imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of stereotactic procedures has been extensively studied [2,3,4,5,6,7,8,9,10,11,12]. However, technology is evolving rapidly in terms of both the surgical equipment and imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The difference reported by Karlsson and colleagues is considerably lower than that observed in our study and this is explained by the methodological differences. The comparison between the pre‐ and post‐GKR scans in their study was done using the calculated mean of repeated observations (mean position of localization), rather than each individual localization attempt, and this could result in erroneously favorable outcomes (2) . Also, we used a different imaging technique before and after GKR, and the imaging slices were also thicker in our study (1.5 vs. 0.7 mm), which explains the increased uncertainty of our measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The application accuracy of four commonly used stereotactic devices, including the Leksell frame, was challenged by Maciunas et al (2) in an attempt to evaluate the total accuracy conveyed by the entire visualization, calculation, and surgical systems working together. The study suggested a significant degree of error in the application accuracy of all the stereotactic instruments tested, but failed to specifically address the question of stability of the frame itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations